2018
DOI: 10.1021/acsami.8b13099
|View full text |Cite
|
Sign up to set email alerts
|

Patterning and Reversible Actuation of Liquid Gallium Alloys by Preventing Adhesion on Rough Surfaces

Abstract: This work reports a simple approach to form, study, and utilize rough coatings that prevent the adhesion of gallium-based liquid metal alloys. Typically, liquids with large interfacial tension do not wet nonreactive surfaces, regardless of surface topography. However, these alloys form a surface oxide “skin” that adheres to many substrates, even those with low surface energy. This work reports a simple approach to render closed channels and surfaces, including soft materials, to be “oxide-phobic” via spray-coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 64 publications
3
105
0
Order By: Relevance
“…Such nonstick and corrosion resistance coating can be applied for a variety of applications, ranging from electrodes (conductive coating) to reconfigurable antennas (nonconductive coating). For example, the rough coating of NeverWet on PDMS was employed for the reversible actuation of liquid metal inside a closed channel, which was employed for an antenna device with adjustable behavior (adjustable operating frequency) …”
Section: Liquid Metal: Category and Naturementioning
confidence: 99%
See 2 more Smart Citations
“…Such nonstick and corrosion resistance coating can be applied for a variety of applications, ranging from electrodes (conductive coating) to reconfigurable antennas (nonconductive coating). For example, the rough coating of NeverWet on PDMS was employed for the reversible actuation of liquid metal inside a closed channel, which was employed for an antenna device with adjustable behavior (adjustable operating frequency) …”
Section: Liquid Metal: Category and Naturementioning
confidence: 99%
“…d) Liquid metal reversible actuation in a NeverWet coated microchannel. Reproduced with permission . Copyright 2018, American Chemical Society.…”
Section: Liquid Metal Microfluidics: Dispersed Microdroplets and Contmentioning
confidence: 99%
See 1 more Smart Citation
“…[47] In addition, although the role of mechanical properties of the substrate on adhesion is not explicitly studied, there are no obvious trends from the data in Figure 2c when comparing adhesion to rigid versus soft substrates. Interestingly, even though Teflon failed the "peck test," our recent studies found that EGaIn can pin to perfluorinated surfaces by advancing the metal against the surface.…”
Section: Choice Of Printing Substratementioning
confidence: 98%
“…Retracting the nozzle reveals if the metal adheres. [46][47][48] Various treatments (deionized water rinsing, UVO exposure for 20 min, silanization, and Soxhlet extraction) are used to modify the surface chemistry and cleanliness. Figure 2a is representative of a "pass" and Figure 2b is representative of a "fail;" i.e., essentially no metal adheres to the substrate.…”
Section: Choice Of Printing Substratementioning
confidence: 99%